Effect of Yoga involvement on mental health in times of crisis: A cross-sectional study - Bös, Christiane; Gaiswinkler, Lisza; Fuchshuber, Jürgen; Schwerdtfeger, Andreas; Unterrainer, Human-Friedrich (Frontiers in Psychology, 2023)
Background: Yoga involvement can be understood as a degree of immersion in the philosophical/spiritual teachings of Yoga. Previous research has shown a positive association between Yoga involvement and mental health. This study further investigates the effect of Yoga involvement on several parameters of psychological well-being and distress amidst a global crisis precipitated by the COVID-19 pandemic. Methods: A total sample of 246 participants (216 females; 118 Yoga versus 128 age-matched Pilates practitioners) were included in the study. Via an online-survey the following questionnaires were completed: the WHO-Five Well-Being Index, the Multidimensional Inventory for Religious/Spiritual Well-Being short version, the Leipzig Short Scale of Sense of Coherence, the Brief Symptom Inventory and the Yoga Immersion Scale which was adapted for the control group to Pilates Immersion Scale. Results: When controlling for occupation and psychiatric disorder, involvement in general was higher for Yoga practitioners than for Pilates controls. Furthermore, Yoga practice was associated with increased religious/spiritual well-being and decreased sense of coherence, but neither with psychological well-being nor with psychological distress. Involvement, in general, positively predicted psychological well-being, religious/spiritual well-being and sense of coherence, but there was no connection with psychological distress. Lastly, involvement mediated the positive relationship between Yoga practice and religious/spiritual well-being and suppressed the negative effect of Yoga practice on sense of coherence. Conclusion: Our findings suggest that involvement in a certain relaxation practice has a positive impact and might be a key component in understanding Yoga's influence on mental health. Further randomized controlled research, including clinical groups, is necessary to explain how involvement changes and how it effects well-being more specifically.